Improving Teachers' Social Competence through Collaborative-Based Teacher Professional Education at UMS Rappang - Suhartini Khalik; M Nurzin K; Suleha; Muhammad Hanafi; Sam Hermansyah; Siti Zulfa (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to explore the enhancement of teachers' social competence through a collaborative-based teacher professional education program at UMS Rappang. Social competence plays a crucial role in fostering effective communication, building positive relationships, and creating a conducive learning environment. The collaborative approach in the program involves interaction among educators, experts, and stakeholders to share knowledge, experiences, and best practices. The research adopts a qualitative methodology, analyzing data collected through observations, interviews, and documentation. The findings indicate that the collaborative-based education model significantly improves teachers' interpersonal skills, adaptability, and professional relationships. These improvements ultimately contribute to a better teaching-learning process and professional growth. This study highlights the importance of collaboration in teacher training programs to develop comprehensive social competence.